Evita, Inevitably : Performing Argentina's Female Icons Before and After Eva Perón - Graham-Jones, Jean, 1958- (Book collections on Project MUSE., 2015)
Evita, Inevitably sheds new light on the history and culture of Argentina by examining the performances and reception of the country's most iconic female figures, in particular, Eva Perón, who rose from poverty to become a powerful international figure. The book links the Evita legend to a broader pattern of female iconicity from the mid-nineteenth century onward, reading Evita against the performances of other female icons: Camila O'Gorman, executed by firing squad over her affair with a Jesuit priest; Difunta Correa, a devotional figure who has achieved near-sainthood; cumbia-pop performer Gilda; the country's patron saint, the Virgin of Luján; and finally, Argentina's president, Cristina Fernández de Kirchner. Employing the tools of discursive, visual, and performance analysis, Jean Graham-Jones studies theatrical performance, literature, film, folklore, Catholic iconography, and Internet culture to document the ways in which these "femicons" have been staged.